Zawsze fragment. O polskim literaturoznawstwie i jego kanonie (Zagłady) - Wolski, Paweł (Narracje o Zagładzie [czasopismo zamknięte], 2015)
Always a fragment. On Polish literary studies and its canon (of the Shoah) The author considers the status of the canon of Holocaust literary studies. Based on Jan and Aleida Assmanns’ well known thesis he proposes to consider this kind of writing as an Encyclopedia – a cumulative reading list of literary studies works considered canonical, and, on the other hand, as a Method, i.e. a model mechanism of creating an analysis and exegesis of the Holocaust writing. The author concludes that despite numerous attempts there is a dominance of canons which fall within the sphere of the first category whereas the second one still awaits fruition. According to the author, a crucial element of the latter would be to define the specific relation between a scholar and the object of his or her research as a particular feature of Holocaust literature and its theory. Key words: Holocaust, literary (meta)criticism, canon